2017
DOI: 10.1002/hep.29499
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine β‐synthase is required for body iron homeostasis

Abstract: Cystathionine b-synthase (CBS) catalyzes the transsulfuration pathway and contributes, among other functions, to the generation of hydrogen sulfide. In view of the exceptionally high expression of CBS in the liver and the common interleukin-6 pathway used in the regulatory systems of hydrogen sulfide and hepcidin, we speculate that CBS is involved in body iron homeostasis. We found that CBS knockout (CBS 2/2 ) mice exhibited anemia and a significant increase in iron content in the serum, liver, spleen, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Altogether, these data imply that the transsulfuration pathway mediated by CBS may interact with the homeostasis of Fe 2+ to disrupt cellular lipid peroxidation, and thus negatively regulates ferroptosis. Interestingly, a recent report indeed observed that knockout of CBS in mice could cause iron-overload and damage in liver 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these data imply that the transsulfuration pathway mediated by CBS may interact with the homeostasis of Fe 2+ to disrupt cellular lipid peroxidation, and thus negatively regulates ferroptosis. Interestingly, a recent report indeed observed that knockout of CBS in mice could cause iron-overload and damage in liver 52 .…”
Section: Discussionmentioning
confidence: 99%
“…As CBS can actively produce H 2 S in retina (Markand et al, 2013;Persa et al, 2006) and brain (Kamat et al, 2015), the age-dependent increase in CBS may link to the antioxidant activity of H 2 S in the retina (George et al, 2018;Sakamoto et al, 2014) and highlight an active role for CBS in H 2 S production compared to CSE. Another explanation for the increased levels of CBS by aging could be because its role in iron hemostasis (Zhou et al, 2018) as increased levels of iron is linked to retinal diseases (Chen et al, 2009) and iron chelation is shown to prevent iron-induced retinal degenerative diseases (Song et al, 2014). We are also interested in studying the role of CBS and CSE in age-and diseasedependent human retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…4 Within the cardiovascular system, H 2 S production, via the catabolism of cysteine by the enzyme CSE, is reported to act as a cytoprotectant against oxidative stress and has distinct functions in inflammatory and apoptotic signaling. 5,6 Moreover, roles for H 2 S gas production in vasorelaxation, 7 the stimulation of angiogenesis, [8][9][10] and protective functions in myocardial ischemia, 11,12 atherosclerosis, 13 anemia, 14,15 hypertension, 16 hypoxia 17 and heart failure 18 have been reported.…”
Section: Introductionmentioning
confidence: 99%